Abbeyknockmoy Cistercian Monastery, north chancel wall, O'Kelly Tomb, jamb and arch - O'Donovan, Danielle (My University, 2008)
Jamb and arch of O'Kelly tomb, the moulding is unusual, and comprises from intrados: hollow chamfer, hollow chamfer, hollow chamfer (forming a kind of polygonal shaft), protruding double roll.
O'Kelly Tomb
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Cistercian; Funerary monuments; Late Medieval; mouldings, hollow; roll mouldings